Komunikasi Publik dalam Mewujudkan Smart Village Melalui Implementasi Layanan Digitalisasi di Desa Jatirenggo Kecamatan Glagah Kabupaten Lamongan - Moch. Farhad Zakaria; Indah Prabawati; Tjitjik Rahaju; Firre An Suprapto (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
The Jatirenggo Village Government, Glagah District, Lamongan Regency, created a digital-based public service innovation through an application, namely the Jatirenggo Online Integrated Service (JALANTOL) application. In the implementation of this application, several problems occurred, namely the community did not fully understand the procedures for using the features in the application, the community still had minimal digital literacy, especially for the elderly, the application features were not fully utilized optimally, especially the complaint feature. This research method used a qualitative descriptive method. The focus of this study used the policy implementation theory from George. C. Edward III which consists of four main indicators, namely communication, resources, position, and bureaucratic structure. Data collection in this study consisted of observation, interviews, and documentation. The results of the study showed that the Implementation of Jatirenggo Online Integrated Services in Jatirenggo Village, Glagah District, Lamongan Regency was not optimal or in accordance with expectations of digital-based public services. Based on the research results, the following suggestions can be given by the researcher: First, in terms of communication, the Jatirenggo Village Government needs to strengthen its socialization strategy to be more systematic, structured, and sustainable. Second, in order to address the low digital literacy of the community, the Jatirenggo Village Government needs to organize regular training and mentoring programs, especially for the elderly community. Third, regarding the suboptimal utilization of application features, especially the complaint feature, it is necessary to optimize the function and increase the attractiveness of using the application. Fourth, it is necessary to provide a clear, centralized, and easily accessible information channel regarding the procedures for using the JALANTOL application.